2002
DOI: 10.1002/bip.10092
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond and picosecond fluorescence of native bacteriorhodopsin and a nonisomerizing analog

Abstract: The spectrally and temporally resolved fluorescence properties of native bacteriorhodopsin (bR) and bR reconstituted with a nonisomerizing analog of the retinal Schiff base (bR5.12) are examined. The first attempt to experimentally monitor the excited state relaxation processes in both type of pigments using ultrafast fluorescence spectroscopy is reported. The fluorescence is emitted from retinal molecules in an all-trans configuration. Substantial energy relaxation involves very fast intramolecular and interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 15 publications
(31 reference statements)
6
24
0
Order By: Relevance
“…We performed a global fitting on thirty curves from 810 to 975 nm. Simultaneous analysis showed two delay time constants of 0.5±0.1 ps (~95%) and 2.0±0.4 ps (~5%), consistent with previous researchers (Figure 2) [7,8,25,[30][31][32] . Analysis of the results showed that the dominant component peaked at ~870 nm with time constant of 0.5 ps, suggesting the character of I 460 .…”
Section: Femtosecond Absorption Spectroscopysupporting
confidence: 91%
“…We performed a global fitting on thirty curves from 810 to 975 nm. Simultaneous analysis showed two delay time constants of 0.5±0.1 ps (~95%) and 2.0±0.4 ps (~5%), consistent with previous researchers (Figure 2) [7,8,25,[30][31][32] . Analysis of the results showed that the dominant component peaked at ~870 nm with time constant of 0.5 ps, suggesting the character of I 460 .…”
Section: Femtosecond Absorption Spectroscopysupporting
confidence: 91%
“…rely on the ultrafast isomerization of the retinal chromophore (1). This process has been intensively investigated by fs pump-probe and f luorescence up-conversion spectroscopy in the visible (VIS) and͞or near-IR (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), revealing the retinal excited-state dynamics before isomerization and the build-up of the isomerized form. Time-resolved VIS-pump͞mid-IR probe experiments on bacteriorhodopsin (bR) established that the isomerization time is Ն400 fs (14).…”
mentioning
confidence: 99%
“…Time-resolved VIS-pump͞mid-IR probe experiments on bacteriorhodopsin (bR) established that the isomerization time is Ն400 fs (14). Indeed, the excited-state lifetime of 300 -500 fs (12,15) goes hand-in-hand with the rise times observed for the 13-cis photoproduct (3,4,14), whereas a longer time scale of 3-4 ps has been attributed to vibrational relaxation of the photoproduct (14).…”
mentioning
confidence: 99%
“…One such imaging method is SWI which was originally developed to image veins and, subsequently, hemorrhage based on the "visible" iron from deoxyhemoglobin [42,43] . We and others have reported on these SWI characteristics [26,44,45] , which provides enhanced imaging capabilities compared to the previously reported T2-, T2 * -weighted or other imaging modalities. We now demonstrate that SWI is capable of accentuating areas containing stem cells.…”
Section: Swi Visualizes Hnscs In the Hii Brain And Tracks Migrationmentioning
confidence: 86%
“…We have used SWI previously for imaging in tumors and in intracerebral hemorrhage [26,44] . These studies and others report a "blooming" effect, wherein the magnetic dephasing effects result in an exacerbation of the lesion size on SWI resulting in areas that are 4-8 times larger than those found on histology [26,46,47] .…”
Section: Swi Visualizes Hnscs In the Hii Brain And Tracks Migrationmentioning
confidence: 99%